THE EFFECTS OF EPS, ROE, PER, NPM, AND DER ON THE SHARE PRICE IN THE JAKARTA ISLAMIC INDEX GROUP IN THE 2014-2017 PERIOD - Budiyono, Budiyono; Santoso, Suryo Budi (Universitas Muhammadiyah Yogyakarta, 2019)
The purpose of this study is to analyze the effect of Earning per Share (EPS), Return on Equity (ROE), Price Earning Ratio (PER), Net Profit Margin (NPM), Debt to Equity Ratio (DER) towards share price. The population used in this study were 30 companies listed in the Jakarta Islamic Index (JII) during the 2014-2017 period. Sampling technique used was non-probability sampling with purposive sampling method and obtained samples of 17 companies per year which are most active in trading in the Jakarta Islamic Index (JII) group during 2014-2017 period. The analytical tool used to test the hypothesis in this study was multiple linear regression analysis using SPSS software. Hypothesis testing results indicate that EPS, ROE, PER, NPM, and DER variables simultaneously have positive and significant effect on share price. Partially, EPS and ROE variables have positive effect on share price. While, NPM have a negative effect on share price, PER and DER have no negative effect on share price, and. R Square testing result showed that the Adjusted R Square is 0.759. It means that 75.9% of the dependent variable which was stock price can be explained by independent variables namely EPS, ROE, PER, NPM, and DER, while the remaining 24.1% is affected by other variables that are not in the linear regression model.